Model E-Sosıometrı untuk Meningkatkan Ketepatan Layanan Bımbıngan dan Koselıng Sosıal di Sekolah Menengah - Ulvina Rachmawati; Sugiyanto Sugiyanto; Mualwi Widiatmoko; Moh Farozin (Indonesian Journal of Educational Counseling, 2026)
This research aims to develop and test the feasibility of an e-sociometry model, awebsite-based e-sociometry model as an instrument for assessing students' needs. This research uses the Borg and Gall model with ten stages but is limited to the fourth stage (feasibility test) due to time and cost considerations. Data collection was carried out through interviews for the preliminary study and expert validation questionnaires to assess the feasibility of the e-sociometry model, while data analysis of the expert validation results used the Aiken's V formula. The interview results revealed technical and analytical constraints in the previous sociometry and that it had not been integrated with Profil Pelajar Pancasila, which is one of the educational goals. Furthermore, the feasibility test showed a score of 0.87, indicating that the e-sociometry model is considered valid or feasible to use. This finding can serve as a solution for guidance and counseling teachers in accurately identifying students' social problems, ultimately leading to the design of appropriate social guidance and counseling services